Malonate inhibits virulence gene expression in Vibrio cholerae. - Yusuke Minato; Sara R Fassio; Claudia C Häse (PLoS ONE, 2013)
We previously found that inhibition of the TCA cycle, either through mutations or chemical inhibition, increased toxT transcription in Vibrio cholerae. In this study, we found that the addition of malonate, an inhibitor of succinate dehydrogenase (SDH), decreased toxT transcription in V. cholerae, an observation inconsistent with the previous pattern observed. Unlike another SDH inhibitor, 2-thenoyltrifluoroacetone (TTFA), which increased toxT transcription and slightly inhibited V. cholerae growth, malonate inhibited toxT transcription in both the wild-type strain and TCA cycle mutants, suggesting malonate-mediated inhibition of virulence gene expression is independent to TCA cycle activity. Addition of malonate also inhibited ctxB and tcpA expressions but did not affect aphA, aphB, tcpP and toxR expressions. Malonate inhibited cholera toxin (CT) production in both V. cholerae classical biotype strains O395N1 and CA401, and El Tor biotype strain, N16961. Consistent with previous reports, we confirmed that these strains of V. cholerae did not utilize malonate as a primary carbon source. However, we found that the addition of malonate to the growth medium stimulated V. cholerae growth. All together, these results suggest that metabolizing malonate as a nutrient source negatively affects virulence gene expression in V. cholerae.